Evolución de las representaciones mentales sobre colisiones - Villani, Alberto; Orquiza de Carvalho, L. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 1997)
The article concerns the results of a qualitative research with secondary school students on the evolution of their ideas about collisions in mechanics. We focus our attention on the mechanism of partial attainment of new ideas and the relationship between the resistance to change and the experimental situations. Some implications for teaching are also discussed.